THE EFFECT OF RATIONAL EMOTIVE THERAPY GROUP COUNSELING ON SELF ESTEEM OF MIDDLE SCHOOL STUDENTS IN SMP NEGERI 27 MEDAN NORTH SUMATRA - Regina Nainggolan; Rafael Lisinus Ginting (Universitas Negeri Medan, 2020)
The purpose of this study was to determine the effect of rational emotive therapy group counseling on the self-esteem of grade VIII students at SMP Negeri 27 Medan. The sample in this study amounted to 7 students who have low self-esteem who were found through the purposive sampling technique. This research is a quasi experimental research with pre-post test one group design. The data were collected using a questionnaire called the self-esteem instrument. There were 57 items tested, then obtained 39 valid items and 18 invalid items. Based on the results of calculations using the Cronbach Alpha formula, it is known that r11 = 0.919 and after being compared with the correlation index, it is concluded that the instrument has very high reliability. Furthermore, the data were analyzed using the Wilcoxon test to see whether there was an effect of rational emotive therapy group counseling on students' self esteem. From the research data, the results of the calculation with the pre-test score in the sample obtained an average = 73.1 while the post-test score obtained an average = 127.71. Data analysis using the Wilcoxon level test obtained J count = 13 while J table = 2.From the critical value table J for the Wilcoxon cascade test for n = 7, α = 0.05 in accordance with the criteria for acceptance and rejection of the hypothesis, the hypothesis is accepted if J count> J table, namely J count> J table where 13> 2 which means the hypothesis is accepted. The results of this study are expected to be the main input for educators to alleviate problems that arise in students due to low self-esteem.